Isolation and evaluation of endophytic fungi with antimicrobial ability from Phyllostachys edulis - Xiaoye Shen; Dongqi Zheng; Jian Gao; Chenglin Hou (Bangladesh Pharmacological Society, 2012)
Endophytic fungi (30) isolates from bamboo branches were categorized into 12 genera, based on the blast analyses of ITS nrDNA sequence in GenBank and microscopic examination. The aim of this work was to investigate the antibacterial and antifungal activities of endophytic fungi. Inhibitory effects against clinical pathogens and phytopathogens have been screened for all the isolates preliminarily and strains tentatively identified as Cladosporium sphaerospermum (PE106), Simplicillium lanosoniveum (PE120), Curvularia sp. (PE127), Didymella sp. (PE128) and Penicillium cf. raistrickii (PE130) presented bioactivity against at least four tested pathogens using the agar diffusion method. Crude extracts of PE106, PE120, PE127 and PE130 displayed broad-spectrum activity against plant pathogenic fungi by mycelial radial growth test. All of the four isolates were found to have high bioactivity against the frequent plant pathogenic fungus Botryotinia fuckeliana, and two of the isolates (PE120 and PE130) also inhibited the growth of phytopathogen Thanatephorus cucumeris noteworthily. This study is the first report on the antimicrobial activity of endophytic fungi associated with branches of Ph. edulis.